Research Progress on Epigenetics of Diabetic Cardiomyopathy in Type 2 Diabetes - Deng, Jianxin; Liao, Yunxiu; Liu, Jianpin; Liu, Wenjuan; Yan, Dewen (Frontiers in Cell and Developmental Biology, 2021)
Diabetic cardiomyopathy (DCM) is characterized by diastolic relaxation abnormalities in its initial stages and by clinical heart failure (HF) without dyslipidemia, hypertension, and coronary artery disease in its last stages. DCM contributes to the high mortality and morbidity rates observed in diabetic populations. Diabetes is a polygenic, heritable, and complex condition that is exacerbated by environmental factors. Recent studies have demonstrated that epigenetics directly or indirectly contribute to pathogenesis. While epigenetic mechanisms such as DNA methylation, histone modifications, and non-coding RNAs, have been recognized as key players in the pathogenesis of DCM, some of their impacts remain not well understood. Furthering our understanding of the roles played by epigenetics in DCM will provide novel avenues for DCM therapeutics and prevention strategies.